2017
DOI: 10.3390/ijms19010107
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Compounds Derived from Natural Supplement as Anticancer Agents in Renal Cell Carcinoma: A Review

Abstract: Renal Cell Carcinoma (RCC) is the most prominent kidney cancer derived from renal tubules and accounts for roughly 85% of all malignant kidney cancer. Every year, over 60,000 new cases are registered, and about 14,000 people die from RCC. The incidence of this has been increasing significantly in the U.S. and other countries. An increased understanding of molecular biology and the genomics of RCC has uncovered several signaling pathways involved in the progression of this cancer. Significant advances in the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 160 publications
(185 reference statements)
0
16
0
Order By: Relevance
“…Anemia is one of the most common clinical features of KD and is considered to be a marker of the acute phase and disease outcome 14 . In one retrospective study, hemoglobin level was found to be the most important indicator for distinguishing KD from the febrile control group 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Anemia is one of the most common clinical features of KD and is considered to be a marker of the acute phase and disease outcome 14 . In one retrospective study, hemoglobin level was found to be the most important indicator for distinguishing KD from the febrile control group 15 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, as shown in Table 3 , EGCG has been most widely used for in vitro studies aiming to clarify the relationship between GTPs and various cancer-related functions. Furthermore, other reports have shown that EGCG is the most important component in terms of the health benefits and anticancer effects of green tea [ 79 , 80 ]. Therefore, ECGC has been the focus of discussion in terms of both potential preventative and of therapeutic approaches for bladder cancer.…”
Section: Bladder Cancer and Green Teamentioning
confidence: 99%
“…Suppression of the inflammatory cascade and subsequent lesser free radical induced cell damage are believed to be one of the major underlying molecular mechanisms of quercetin against cancer. The impact of chronic inflammation in carcinogenesis is well established and strong anti-cancer effects of quercetin are reflected by as many as 2700 publications in PubMed as of February 2019 when combining "quercetin and cancer" in searches and reviewed elsewhere (Gibellini et al, 2011;Haque et al, 2017;Kashyap et al, 2016;Khan et al, 2016;Nam et al, 2016).…”
Section: Mechanism Experimental Model Referencementioning
confidence: 99%
“…Besides strong anti-inflammatory bioactivities, proapoptotic effects of quercetin are conceivably the basis for chemoprotective and/or therapeutic effects in different cancers. The activation of apoptotic pathways by quercetin in various cancers during different cell cycle stages has been documented in vitro as well as in vivo (Gibellini et al, 2011;Granado-Serrano et al, 2010;Haque et al, 2017;Lee et al, 2010). For adenocarcinoma, breast, colon, lung and myeloid cancer, it has been demonstrated that apoptotic signaling by quercetin is triggered via caspase-3 activation through mechanisms of the mitochondrial-mediated pathway (Chien et al, 2009;Han and Zhang, 2016;Lee et al, 2015;Srivastava et al, 2016;Volate et al, 2005;Yang et al, 2006).…”
Section: Mechanism Experimental Model Referencementioning
confidence: 99%
See 1 more Smart Citation